Dynamic ECG Changes in a Patient with High Altitude Pulmonary Edema - Ahuja, Taruna; Dey, Himadri Shekhar; Dutt, Sachin; Dewangan, Danesh Kumar (Journal of Contemporary Medical Practice, 2025)
High Altitude Pulmonary Edema (HAPE) is a severe and potentially fatal condition affecting travellers and military personnel at high elevations. It primarily results from hypoxic pulmonary vasoconstriction leading to increased pulmonary artery pressure. This case report describes a 30 - year - old male who developed HAPE after a rapid ascent to 3500m and subsequent descent to 2676m. Despite clinical improvement with oxygen therapy and medication, dynamic electrocardiogram (ECG) changes suggestive of right ventricular strain were observed. The findings highlight the potential cardiac involvement in HAPE, which can complicate diagnosis and necessitate extensive cardiac evaluations. Understanding such ECG changes can aid clinicians in distinguishing HAPE from other cardiac emergencies, ensuring timely and appropriate management while avoiding unnecessary resource utilization.